Effect of Knowledge-Based Human Resources Management on Organizational Learning Ability: Mediating Role of Intellectual Capital - سعید صحت; مصطفی آقائی; سیروان شریفیان (مطالعات منابع انسانی, 2019)
Background and Objective: The continuous retention of organizational learning ability is among the prerequisites for the sustainable productivity of leading organizations. Therefore, this study aimed to analyze the mediating role of intellectual capital on the effect of knowledge-based human resources management on organizational learning ability. Methodology: This is a descriptive correlational study, in which the statistical population included the 216 companies operating in Bu Ali Industrial Town of Hamadan. The simple random sampling method was employed to select 138 companies as the statistical sample. A questionnaire was used for data collection, and the partial least square structural equation modeling (PLS-SEM) technique was utilized for data analysis in SmartPLS2. Findings: All three components of intellectual capital played a mediating role in the effect of knowledge-based human resources management on organizational learning ability. In this regard, human capital plays the most important role, whereas structural capital plays the least important role. Conclusion: Using the knowledge-based human resources management can increase the dimensions of intellectual capital and indirectly improve the organizational learning ability.